The Effect of Psychological Contract Combined With Stress and Health on Employees’ Management Behavior - Cheng, Yueyuan (Frontiers in Psychology, 2021)
In order to effectively manage employees and improve their work enthusiasm, based on the theoretical basis of project team members' psychological contract, the status quo of employees' psychological contract, stress and health status are investigated and analyzed. The differences of employees' psychological contract are analyzed through the questionnaire. A total of 400 questionnaires are distributed and 365 are returned. The method of one-way ANOVA is used to study the psychological contract status of project members from four aspects: gender, education background, position level and working years, and obtain the results of difference analysis in four aspects. Functional magnetic resonance imaging (fMRI) is used to evaluate the work stress of employees. The results show that gender, education background, position level and working years have different effects on employees' psychological contract. Moreover, if employees continue to bear high-intensity work stress, a series of psychological and physical health problems will appear, such as difficulty in concentration. For enterprises, the poor psychological and physical conditions of employees will make the overall work inefficient and the working atmosphere dull. Therefore, enterprises should control employees' work stress within a reasonable range, and should not blindly impose high-intensity work stress on employees. This exploration demonstrates the way to realize the psychological contract construction of project team members, and targeted employee management countermeasures are put forward.